Performance Appraisal (International Journal of Scientific Research and Management (IJSRM), 2015)
People differ in their abilities and their aptitudes. There is always some difference between the quality and quantity of the same work on the same job being done by two different people. Performance appraisals of Employees are necessary to understand each employee’s abilities, competencies and relative merit and worth for the organization. Performance appraisal rates the employees in terms of their performance. Performance appraisals are widely used in the society. The history of performance appraisal can be dated back to the 20th century and then to the second world war when the merit rating was used for the first time. An employer evaluating their employees is a very old concept. Performance appraisals are an indispensable part of performance measurement.